2012
DOI: 10.1016/j.ijsu.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

A study on 107 patients with acute mesenteric ischemia over 30 years

Abstract: Acute mesenteric ischemia (AMI) is a life threatening cause of acute abdomen. The purpose of this study is to define risk factors that predict the adverse outcome of AMI and to present our experience in the last 30 years. Hospital records and clinical data of 107 patients undergoing surgical intervention for AMI during the last 30 year period were reviewed and clinical outcomes as well as factors influencing mortality were analyzed. Mesenteric arterial thrombosis, arterial embolism and nonocclusive mesenteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 23 publications
4
64
1
4
Order By: Relevance
“…A large majority of these studies, like ours, have a retrospective design (14,15). The absence of a specific method for the diagnosis of AMI generally results in delayed diagnosis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A large majority of these studies, like ours, have a retrospective design (14,15). The absence of a specific method for the diagnosis of AMI generally results in delayed diagnosis.…”
Section: Discussionmentioning
confidence: 96%
“…Fluid resuscitation, invasive hemodynamic monitoring, prophylactic antibiotherapy, systemic anticoagulation, resection of ischemic and necrotic intestinal loops, restoration of blood supply, consideration of short bowel syndrome in terms of remaining intestine length, and critical intensive care are all essential components of treatment (14). The operative technique performed is directly related to the affected intestinal loop, and the extent of involvement has been reported to effect mortality.…”
Section: Treatmentmentioning
confidence: 99%
“…A 2012 analysis by Alhan et al revealed a hospital mortality rate of 55.1%. Diabetes, digoxin and antiplatelet therapy, prolonged symptom duration, shock, acidosis, and re-laparotomy were all negative predictors of mortality 5 . ACS-NSQIP is the first nationally validated, riskadjusted, outcomes-based program to measure and improve the quality of surgical care.…”
Section: Introductionmentioning
confidence: 96%
“…1 Since the affected site, range and severity varies, AMAE has complex and variable clinical symptoms and signs, laboratory tests and imaging manifestations, and its early diagnosis is very difficult because of overlapping manifestations with primary diseases. 2,3 Recent great advances in multislice CT (MSCT) have encouraged research into the diagnosis of AMAE.…”
Section: Introductionmentioning
confidence: 99%